Shariah compliance and balanced scorecard measures for performance of Malaysian Islamic Banks using Rasch model / Nik Aiman Nik Muhamad - Nik Muhamad, Nik Aiman (2015)
The assessment of Islamic banks performance is still underexplored thus limiting a better perspective of performance evaluation for Islamic banking as a whole.Improvements are needed to further enhance the quality and performance of their products and services. This study enhanced the Balanced Scorecard (BSC) model based on the attributes of Kaplan and Norton’s BSC (1992, 1996, 2001). The model was operationalized using a survey that was administered to the Islamic banking personnel. The thesis attempted to answer three research questions: (1) What are the attributes from the integration of BSC and Shariah Compliance measures used in the performance measurement system of Malaysian Islamic Banks?; (2) What is the relationship between Shariah Compliance and BSC measures with the performance of Islamic banks?; and (3) What are the Shariah Compliance and BSC measures used by the successful Islamic banks? This study conceptualized Kaplan and Norton’s (1996, 2001) Balanced Scorecard and comparing this to the performance measurement systems of Malaysian Islamic banks. The study also introduced a guideline of Shariah Compliance and BSC measures to be used by Islamic banks in order to improve their performance. This study was done with a slight difference in conceptualization of Kaplan and Norton’s BSC and applied to a Malaysian setting namely Islamic banks. From the findings, there was a positive relationship between BSC measures, Shariah Compliance attributes and Islamic banking performance. Banks which used all the BSC and Shariah measures in the study also known as exemplar improved their performance tremendously. A structure for performance measurement were introduced as a guideline for Islamic banks potential use to enhance and increase their performance.